Alteridade e idéia de nação na passagem à modernidade: o círculo Rio Branco no Brasil "Ubique Patriae Memor" - Silva, Daniella Amaral Diniz da (2008)
This work studies the idea of nation in Brazil at the turn of the Twentieth Century and the political agendas and principles of the Foreign Affairs Ministry s policies concerning border issues and policies of cooperation between Latin American countries among intellectuals. I examine the works of some members of the group of intellectuals that were part of the Foreign Affairs Ministry - formally and informally - between 1902 and 1912, a period in which Barão do Rio Branco was the Minister of Foreign Affairs in Brazil. In addition, I investigate the relationship between some of these intellectuals and diplomats and their portrayals of Rio Branco as an intellectual and politician in letters and correspondences. I analyze these individuals coresspondences in order to better understand how these intellectuals and politicians perceived issues such as progress, alterity, intellectuality, diplomacy, and history.